(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2026)
The article examines the economic mechanisms for the development of small business entities and their regional effectiveness using the example of Tashkent city and the Tashkent region. The study provides a comparative analysis of industrial production volumes and employment dynamics for the period 2020–2024, evaluating financial, tax, and institutional support tools. Based on the findings, scientific conclusions and practical recommendations are formulated to enhance the role of small entrepreneurship in regional economic growth.